Beyond economic growth: The role of trade unions in the transition to well-being - Peter Nitsche-Whitfield (European Trade Union Institute (ETUI), 2023)
It is widely accepted that the pursuit of economic growth is becoming increasingly infeasible and undesirable, necessitating substantial changes to European economies. European economic activity in terms of emissions, resource use, pollution and impacts on biodiversity is ecologically unsustainable. In the face of tipping points soon to be reached and cascading, inter-related ecological crises, the impacts of economic activities need to fall rapidly and substantially to avert disaster. It is no longer possible to decouple growth from ecological impacts sufficiently within the required timespan. Furthermore, even disregarding the necessity to reduce ecological impacts, a multitude of reasons - from energy crises to demographic change - are leading many economists to question European growth prospects. In any case, curbing ecologically damaging practices will be key to addressing the multiple crises Europe is facing. The pursuit of evermore undifferentiated GDP growth will therefore not deliver for working people in terms of well-being and social progress. GDP is particularly unsuitable for measuring the benefits of public services and accounting for inequality. Therefore, trade unions should strengthen their collaboration with the growing group of actors calling for a move beyond growth and a focus on well-being. Public services are key in this, as their collective nature minimises ecological impacts while improving the well-being of more people. Universal basic services provided on a collective basis have substantially smaller ecological footprints than providing for the same needs on an individual basis. Public services can also provide good-quality and meaningful jobs. Universal basic services should be an inalienable part of any just transition, as they are at the core of strong and effective social protection systems. Lastly, focusing on universal quality public services has the added benefit of making economies less reliant on economic growth for securing well-being. A labour-nature alliance will be indispensable to bringing about a social-ecological transformation beyond growth. Actions of solidarity between environmentalists and trade unionists are thus an important step to a better future. Trade unions can play a unique role in developing narratives showing how a Europe moving beyond GDP and towards redistribution and social justice could improve lives and livelihoods across the continent.
Keywords: 330; Steady-State-Ökonomie; Sozialer Wandel; Nachhaltige Entwicklung; Gewerkschaftspolitik; Universaldienst; Öffentliche Dienstleistung; Grundeinkommen; EU-Staaten